Referência linguística e descolonização de nomes próprios em línguas de sinais - Escobar Lopez Dellamary, Luis Daniel (2024)
The subject of the proper name is the subject of reference. Proper names are paradigmatic examples because they refer to unique entities in the world (uniqueness). In sign languages, there are gestural expressions that identify people in deaf communities and are distinguished from the spelling of their name given in Latin alphabet. Studies on this topic have described the signed proper name according to hand configurations and its other articulatory characteristics, according to some general principles about the significance of having the proper name in the community and how it functions. However, almost no mention is made of the basic concepts involved in the theoretical formulation of names and uniqueness. In this paper, we argue that descriptions of this topic are deliberately simplistic and reductionist, not because there is a desire to marginalize sign languages, but because we have been historically conditioned to act this way. From a decolonial critique and an anti-representationalist perspective of language, we show the controversies that shape the issue of proper names and propose an integrated view that advances in the deconstruction of polarizations and false dichotomies in the linguistic and identity discourse.